Optimization of compressive strength for Aceh Besar traditional bricks using Box-Behnken design - Arifin, Riski; Rahmawati, Sri; Annisa, Sitti (Universitas Sultan Ageng Tirtayasa, 2025)
Traditional brick production in Aceh Besar remains inconsistent in quality, particularly regarding compressive strength, which often does not meet the minimum requirement set by the Indonesian National Standard (SNI 15-2094:2000). This inconsistency is mainly due to the absence of standardized raw material formulations and controlled production methods. This study aims to determine the optimal combination of production variables to improve the compressive strength of traditional bricks. To solve this problem, the Response Surface Methodology (RSM) with a Box Behnken Design was employed to examine five key factors: clay, sand, water, drying time, and firing duration. A total of 46 experimental trials were conducted based on the design matrix. The results show that clay and water significantly affect compressive strength, while sand, drying time, and firing duration do not significantly impact. The optimal combination—1600 grams of clay, 600 grams of sand, 600 ml of water, 15 days of drying, and 94 hours of firing—produced a compressive strength of 76.141 kgf/cm². These findings contribute to improving traditional brick production by offering a data-driven approach to achieving higher quality and compliance with national standards.